Modeling and Simulation Tools for Supercritical Fluid Processes - Díaz, María Soledad (2000)
The application of an upgraded group contribution equation of state combined with rigorous simulation and optimization to supercritical processes is reviewed and new applications are presented for vegetable oil purification and separation of fatty acid alkyl esters.